RC48-ADC combined with tislelizumab as neoadjuvant treatment in patients with HER2-positive locally advanced muscle-invasive urothelial bladder cancer: a multi-center phase Ib/II study (HOPE-03) - Wen, Feng; Lin, Tianhai; Zhang, Peng; Shen, Yali (Frontiers in Oncology, 2024)
Background Bladder cancer with high expression of human epidermal growth factor receptor-2 (HER2) is related to pathological malignancy and poor prognosis. The standard care for muscle-invasive urothelial bladder cancer (MIBC) is neoadjuvant chemotherapy (NAC) followed by radical cystectomy (RC) with pelvic lymph node dissection. For HER2-positive MIBC, the efficacy of cisplatin-based NAC is unsatisfactory, and adverse reactions are inevitable or even intolerable. New regimens with higher efficiency and lower toxicity need to be explored in the neoadjuvant setting for this population. Methods HOPE-03 is a multi-center, open-label, single-arm, phase Ib/II study aiming to evaluate the safety and efficacy of RC48-ADC (disitamab vedotin (DV)), a humanized anti-HER2 antibody conjugated with monomethyl auristatin E, and tislelizumab (PD-1 antibody) as a novel neoadjuvant treatment combination in patients with HER2-positive locally advanced urothelial MIBC. Fifty-one patients with cT2-4bN0-3M0-1a pathology- and imaging-diagnosed HER2 positive (immunohistochemistry status 3+ or 2+ or 1+) MIBC were recruited. Of these patients, six were enrolled in the dose-escalation phase (three patients in the RC48-ADC 1.5 mg/kg group and three patients in the 2.0 mg/kg group), and 45 patients were enrolled in the phase II study (the expected recommended phase II dose for RC48-ADC was 2.0 mg/kg). Patients without disease progression received radical cystectomy or bladder-sparing therapies as their preference after neoadjuvant treatment. The primary endpoints were clinical complete remission rate (cCR rate; T0/Ta/Tis), pathological complete remission rate (pCR rate), and safety. The secondary endpoints were overall survival (OS), local recurrence-free survival (LRFS), distant metastasis-free survival (DMFS), and quality of life. Discussion The HOPE-03 trial provides a description of the safety profile of RC-48 and tislelizumab combination in the neoadjuvant treatment of HER2-positive locally advanced urothelial MIBC, and the efficacy is explored as well in this population. Clinical trial registration https://www.chictr.org.cn/showproj.html?proj=137111, identifier ChiCTR2200060153.